what is the size of the moon in milimeters? (area) (answer)
The diametre of the moon is 3474km. Convert that into millimetres and you get 3.474X109mm. The surface area of a spherical object is 4πr2/3, and I'll leave that part for you to calculate.
The diametre of the moon is 3474km. Convert that into millimetres and you get 3.474X109mm. The surface area of a spherical object is 4πr2/3, and I'll leave that part for you to calculate.
0.1 (t + 0.5) + 0.2t = 0.3 (t - 0.4); 0.1t + 0.05 + 0.2t = 0.3t - 0.12; 0.3t + 0.05 = 0.3t - 0.12; 0.05 = 0.12 which is obviously not true. Hence there is no solution to this problem.
So when the problem is saying that 3 out of every 8 students prefer strawberry to vanilla, it means that 3/8 of all students like strawberry better. There are 160 students in total, so that means 3/8 * 160 or 60 students like strawberry.
0.1 (w + 0.5) + 0.2w = 0.2(w - 0.4); 0.1w + 0.05 + 0.2w = 0.2w - 0.08; 0.1w + 0.05 = -0.08; 0.1w = -0.13; w = -1.3
Can you please write it in mathematical notation? What you have can be interpreted multiple ways.
(x2+1)(x+2) = x2(x+2) + 1(x+2) = x3 + 2x2 + x + 2
I often run into people who have a hard time completing their math homework; usually, when I ask them what's going wrong, they say that they don't know where to start tackling the problem. It's not really their fault because sometimes, the same thing happens to extremely hard-working individuals; I've seen a few ambitious straight-A students take much more time on a homework problem than needed... read more
In my opinion, drugs cannot substitute a good night's sleep.
Destiny, I'll assume that the "_>" in your question means "greater than or equal to" (it's usually written >= on a computer). 4 + 2 (-8p - 1) >= -94; -16p - 2 >= -98; -16p >= -96; p <= 6. (Remember, if you're dividing by a negative in an...
You're conflating a number of scientific concepts and trying to throw philosophy in between, so your question doesn't allow for an answer.
Am I asked to factor it or what?
(3 - 2i) / (1 - i) = [(3 - 2i)(1 + i)] / (1 - i)( 1 + i) = (3 + 3i - 2i - 2i2) / (1 - i2) = (5 + i) / 2
When you see stuff like xa * xb * xc * xd, the answer is always x(a+b+c+d). Hence the answer in this case is x(2 + 3 + 5 + 0) = x10.
Hello Janie. Since you didn't get the right answer by taking answers out of the bank, let's try a solution method that doesn't involve guess-and-check. 5 (x + 3) - (4x - 6) = -4; 5x + 15 - 4x + 6 = -4; x + 21 = -4; x = -25. So your not finding an answer is...
You use the same principles as if there's only one inequality sign. But if it makes it easier for you, divide the problem into two separate inequalities: -1 < 3 - 5m < 3 is the same thing as saying that -1 < 3 - 5m and 3 - 5m < 3. Now, normal inequality rules apply. First...
The basic idea is to divide both numerator and denominator by the factors that they share: 18/24 = (3 * 6) / (4 * 6) = 3/4. Here, 6 is the shared factor. 7rs3/21r2s = (7 * rs * s2) / (3 * 7 * rs * r) = s2 / 3r. Here, 7rs is the shared factor. 1/4 * 24x = 24x / 4 = 6x. Here, the shared...
Well...surely 105 > 75, no?
See how the two points have the same x-value (-3)? That means it's a vertical line and comes in the form of x = something. Here, that something is -3. It's not possible to write vertical lines in slope-intercept form, so x = -3 would be the answer to your question.
I found an alternative answer. We can first factor (2s - 3)/(s2 - 4) into A/(s+2) + B(s - 2). By the solution methods in your book, you should get A = 7/4 and B = 1/4. We know that F(s) = A/(s - a) means that f(t) = e-at, so what you should get for the answer is f(t) = 7/4 * e-2t...
Does there have to be 4 steps?